UPAYA MENINGKATAN PRESTASI BELAJAR SISWA MELALUI MODEL PEMBELAJARAN EXAMPLES NON EXAMPLES PADA MATA PELAJARAN BAHASA INDONESIA SISWA KELAS IX SMP NEGERI 2 LUBUK PAKAM - Rita Masdiana Manurung; Florida Simatupang (Jurnal Dedikasi Pendidikan, 2021)
This classroom action research aims: 1) To determine the application of the Examples Non Examples Model in improving students’ skills in compiling the text structure reports; 2) To determine the increase in compiling the text structure of the report in improving the students' skills in compiling the text structure of the report through the application of Model Examples Non Examples This research was conducted using an interactive qualitative model and a class action research approach to PTK (class action research) which was conducted in 2 cycles. Each cycle included planning, implementing, observing and reflecting. The subjects of this classroom action research were students of class IX.8 odd semester SMP Negeri 2 Lubuk Pakam Kab. Deli Serdang. The results indicated that there was an increasing in the learning outcomes achieved by students in mastering the material. Based on the data analysis, it can be concluded that in cycle 1 the students' learning completeness in this material was only 63.00, while in cycle 2 by applying the Examples Non-Examples Model learning strategy increased in cycle 2 the average value increased to 77.67.